The Forecasting Analysis of Rice Production and Sufficiency Consumption of Rice (Oriza sativa) in Konawe District - Aminah Tuzu Rianti; Azhar Bafadal; Abdi Abdi (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
Rice is an essential food crop because rice is still used as a staple food and is a strategic commodity in Indonesia. The availability of affordable rice for the community is one of the key factors in national security. Food crop production forecasts are needed to support government policies in overcoming food problems, especially rice in Indonesia. This study aims to determine the estimates for the amount of rice production in Konawe Regency in the future by using the Least Squares method, knowing the adequacy of rice in Konawe Regency. This research was conducted in Konawe Regency, Southeast Sulawesi, from May to December 2021. The data source used in this study was secondary data obtained from the Southeast Sulawesi Central Statistics Agency (BPS) and the Agriculture Service. Data on the rice production in Konawe Regency for the 2000-2020 period. From the simulations carried out using the Least Squares model, it is obtained that the forecasting results of rice production in Konawe Regency will continue to increase from year to year for the next ten years (2021-2030). The average increase in rice production in the next ten years is 1.60% per year, with the Konawe Regency rice consumption need in 2020 of 49,594.08 tons. Based on rice production and demand, the total availability of rice in Konawe Regency in 2021 is 74,585.5 tons, indicating a status of surplus rice availability. Determination of the accuracy of forecasting rice production in Konawe Regency is calculated using the Mean Absolute Percentage Error (MAPE) which produces a relatively small error value of 1.3%.